A study on customers satisfaction on Perodua cars/ Bibiana Thomas Manggang - Thomas Manggang, Bibiana (2007)
This research attempts to analyze the customer satisfaction on Perodua car. The main objectives of this study are to determine to what extent customers are satisfied or not satisfied with Perodua car and to determine what are the factors that influence the selection of car when a customer wants to decide to purchase a car. Then based on the result findings, recommendations will be provided at the end of this report on how Perodua should make improvements to fulfill its customer’s satisfaction.